The Effect of Low Impact Aerobic Gymnastics on Blood Pressure in Elderly Patients with Hypertension at Mariat Community Health Care Centre, Sorong Regency - Arobaya, Flora Riska; Simon, Merlis Simon; Fitriani, Fitriani; Tyas, Lusia Wahyuning (Fakultas Kedokteran, 2024)
Background: According to the World Health Organization (2023) more than 30% of the adult population worldwide has hypertension. Based on the Indonesian Health Survey (2023) states that the prevalence of hypertension from the diagnostic results of doctors obtained the results of 638,178 cases of hypertension in Indonesia. A total of 123 out of 272 elderly people at the Mariat Health Center (2022) were diagnosed with hypertension. Hypertension is a silent killer, one of the etiological factors of hypertension is lack of exercise. One of the treatments for hypertension is sports training, especially aerobic types. Objective: This study aims to determine the effect of low impact aerobic exercise on blood pressure in the elderly at the Mariat Health Center, Sorong Regency. Methods: This type of research is quantitative research with pre-experiment method and one group design (pretest-postest) without control or comparison group. The population in this study were all elderly groups (pre-elderly, elderly and at-risk lasia) with hypertension who participated in low impact aerobic exercises at the Mariat health center as many as 60 respondents with a sample of the results of purposive sampling of 50 respondents. The research was conducted at the Mariat Health Center of Sorong Regency in January 2023, the instruments used were observation sheets, gymnastics soup, Sphygmomanimeter. Results: The results of the Wilcoxon test obtained the value of a systolic and diastolic blood pressure = 0.000 < a = 0.05 which means p < a. Conclusion: The conclusion of this study is that there is an effect of low impact aerobic exercise on changes in blood pressure of the elderly at the Mariat Health Center. Suggestions for the Mariat Health Center to hold gymnastics 2x / week and routinely with the aim of helping the elderly maintain a healthy body and also as a prevention of hypertension.